Migration [videorecording (DVD)] - Renner, Benjamin, 1983-; White, Mike, 1970-; Powell, John, 1963- (Universal, 2024)
The Mallard family is in a bit of a rut: while dad Mack is content to keep his family safe paddling around their New England pond forever, mom Pam is eager to shake things up and show their kids - teen son Dax and duckling daughter Gwen - the whole wide world. After a migrating duck family alights on their pond with thrilling tales of far-flung places, Pam persuades Mack to embark on a family trip, via New York City, to tropical Jamaica.